Plaintiffs exploiting Plaintiffs - Alexander Stremitzer (University of Bonn, Bonn Graduate School of Economics (BGSE), 2008)
We consider a model of a single defendant and N plaintiffs where the total cost of litigation is fixed on the part of the plaintiffs and shared among the members of a suing coalition. By settling and dropping out of the coalition, a plaintiff therefore creates a negative externality on the other plaintiffs. It was shown in Che and Spier (2007) that failure to internalize this externality can often be exploited by the defendant. However, if plaintiffs make sequential take-it-or-leave-it settlement offers, we can show that they will actually be exploited by one of their fellow plaintiffs rather than by the defendant. Moreover, if litigation is a public good as is the case in shareholder derivative suits, parties may fail to reach a settlement even having complete information. This may explain why we observe derivative suits in the US but not in Europe.
Keywords: K41; C7; H4; 330; litigation; settlement; bargaining; contracting with externalities; derivative suits; public goods; Zivilprozess; Verhandlungstheorie; Vertragstheorie; Externer Effekt; Öffentliches Gut; Theorie